Rice ubiquitin‐conjugating enzyme OsUBC26 is essential for immunity to the blast fungus Magnaporthe oryzae. (30th August 2021) - Liu, Xin; Song, Linlin; Zhang, Heng; Lin, Yijuan; Shen, Xiaolei; Guo, Jiayuan; Su, Meiling; Shi, Gaosheng; Wang, Zonghua; Lu, Guo‐Dong
Abstract: The functions of ubiquitin‐conjugating enzymes (E2) in plant immunity are not well understood. In this study, OsUBC26, a rice ubiquitin‐conjugating enzyme, was characterized in the defence against Magnaporthe oryzae . The expression of OsUBC26 was induced by M. oryzae inoculation and methyl jasmonate treatment. Both RNA interference lines and CRISPR/Cas9 null mutants of OsUBC26 reduced rice resistance to M. oryzae . WRKY45 was down‐regulated in OsUBC26 null mutants. In vitro E2 activity assay indicated that OsUBC26 is an active ubiquitin‐conjugating enzyme. Yeast two‐hybrid assays using OsUBC26 as bait identified the RING‐type E3 ligase UCIP2 as an interacting protein. Coimmunoprecipitation assays confirmed the interaction between OsUBC26 and UCIP2. The CRISPR/Cas9 mutants of UCIP2 also showed compromised resistance to M. oryzae . Yeast two‐hybrid screening using UCIP2 as bait revealed that APIP6 is a binding partner of UCIP2. Moreover, OsUBC26 working with APIP6 ubiquitinateds AvrPiz‐t, an avirulence effector of M. oryzae, and OsUBC26 null mutation impaired the proteasome degradation of AvrPiz‐t in rice cells. In summary, OsUBC26 plays important roles in rice disease resistance by regulating WRKY45 expression and working with E3 ligases such as APIP6 to counteract the effector protein AvrPiz‐t from M. oryzae . Abstract : Rice ubiquitin‐conjugating enzyme OsUBC26 is essential for immunity to blast fungus by regulating WRKY45 expression and working with APIP6 to promote the ubiquitination and degradation of AvrPiz‐t.